VC: HIGHLIGHT SCHOLARS’ VIEWS TO ENHANCE SELFWORTH AND PROMOTE NATION BUILDING - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, September 2015 – The Media and Public Relations Centre, Universiti Sains Malaysia (MPRC USM) has been called upon to gather the views and opinions of the country’s prominent scholars, especially those who have been long involved in the nationbuilding and development process, in order to enhance the sense of selfworth within the community and to provide more clarity to the information on efforts relating to the development of the society and the country.